Predictors of Cardiovascular Affection in Patients with Active Rheumatoid Arthritis: Secondary Analysis of a Randomized Controlled Trial - Ibrahem, Eman M.; El-gendi, Salwa S.; Mahmoud, Amal A.; Abdel-Aal, Sherif M.; El Nouby, Fatma H.; El-Deen Mohammed, Hanan S. (Current Rheumatology Reviews, 2021)
Objective: This is a secondary analysis of a randomized controlled trial that aimed to assess subclinical atherosclerosis in patients with rheumatoid arthritis (RA) by measuring carotid artery intima-media thickness (CIMT) and correlating it with disease activity and inflammatory markers (including levels of matrix metalloproteinase-3(MMP-3) and matrix metalloproteinase-9 (MMP-9)) and to detect the effectiveness of agents that inhibit matrix metalloproteinases (MMPs) as doxycycline in RA therapy. Methods: One hundred and sixty RA patients were assigned in a randomized clinical trial (clinicaltrial. gov NCT03194204). Disease activity score 28(DAS28), laboratory markers, including erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), MMP-3, and MMP-9 were evaluated and mean CIMT was measured. Subjects were allocated randomly into one of two treatment arms, either methotrexate (MTX) alone or MTX with doxycycline 200mg per day orally. Follow up ESR, CRP, DAS28, MMP-3, and MMP-9 levels were re-evaluated after 3 months. Results: There were positive significant correlations between CIMT and disease duration (r = 0.461, p = 0.001), age (r=0.459, p= 0.001), DAS28 score (r= 0.547, p = 0.001), ESR (r =0.413, p = 0.001), CRP (r = 0.281, p = 0.001), MMP-3 (r = 0.476, p = 0.001), and MMP-9 (r = 0.593, p =0.001). Patients treated with MTX and doxycycline showed lower levels of DAS28, ESR, CRP, MMP-3, and MMP-9 and this was statistically significant. Conclusion: CIMT seems to be the ultimate method to screen for subclinical atherosclerosis in RA patients. MMP-3 and 9 play a key role in both RA synovitis and cardiovascular changes, making them important therapeutic targets, especially with safe and cost-effective agents like doxycycline. This clinical trial was carried out in Assiut University Hospital (AUH), Assiut, Egypt (Clinical Trial Registration No. clinicaltrial.gov NCT03194204).
Keywords: combination therapy